High-cycle fatigue cracks in concrete investigated by CT tomography - Miarka, Petr; Seitl, Stanislav; Klusák, Jan; Malíková, Lucie; Merta, Ildiko; Bílek, Vlastimil (Elsevier, 2023)
This contribution deals with the analysis of fatigue damage in high-performance concrete (HPC) studied by three-point bending test. The concrete sample was tested with frequency of 10 Hz and it was exposed to a total number of load cycles 2×106. The internal structure and damage localization was studied by CT tomography. Found locations of internal damage i.e., cracks, were discussed.

This contribution deals with the analysis of fatigue damage in high-performance concrete (HPC) studied by three-point bending test. The concrete sample was tested with frequency of 10 Hz and it was exposed to a total number of load cycles 2×106. The internal structure and damage localization was studied by CT tomography. Found locations of internal damage i.e., cracks, were discussed.
High-cycle fatigue cracks in concrete investigated by CT tomography
Keywords: Fatigue; concrete; HPC; CT tomography.; Fatigue; concrete; HPC; CT tomography.